Neuropathic pain: Mechanisms and therapeutic strategies - Petroianu, Georg A.; Aloum, Lujain; Adem, Abdu (Frontiers in Cell and Developmental Biology, 2023)
The physiopathology and neurotransmission of pain is of an owe inspiring complexity. Our ability to satisfactorily suppress neuropathic or other forms of chronic pain is limited. The number of pharmacodynamically distinct and clinically available medications is low and the successes achieved modest. Pain Medicine practitioners are confronted with the ethical dichotomy imposed by Hippocrates: On one hand the mandate of primum non nocere, on the other hand the promise of heavenly joys if successful divinum est opus sedare dolorem. We briefly summarize the concepts associated with nociceptive pain from nociceptive input (afferents from periphery), modulatory output [descending noradrenergic (NE) and serotoninergic (5-HT) fibers] to local control. The local control is comprised of the “inflammatory soup” at the site of pain origin and synaptic relays stations, with an ATP-rich environment promoting inflammation and nociception while an adenosine-rich environment having the opposite effect. Subsequently, we address the transition from nociceptor pain to neuropathic pain (independent of nociceptor activation) and the process of sensitization and pain chronification (transient pain progressing into persistent pain). Having sketched a model of pain perception and processing we attempt to identify the sites and modes of action of clinically available drugs used in chronic pain treatment, focusing on adjuvant (co-analgesic) medication.